Coated Zinc Oxide Improves Growth Performance of Weaned Piglets via Gut Microbiota - Sun, Yiwei; Ma, Ning; Qi, Zengkai; Han, Meng; Ma, Xi (Frontiers in Nutrition, 2022)
Weaned piglets stayed in transitional stages of internally organic development and externally environmental change. The dual stresses commonly caused intestinal disorders followed by damaged growth performance and severe diarrhea. High dose of zinc oxide could improve production efficiency and alleviate disease status whereas caused serious environmental pollution. This research investigated if coated ZnO (C_ZnO) in low dose could replace traditional dose of ZnO to improve the growth performance, intestinal function and gut microbiota structures in weaned piglets. A total of 126 cross-bred piglets (7.0 ± 0.5 kg body weight) were randomly allocated into 3 groups and fed basal diet or basal diet supplemented with ZnO (2000 mg Zn/kg) or C_ZnO (500 mg Zn/kg), respectively. The test lasted for 6 weeks. C_ZnO improved average daily gain (ADG) and feed efficiency, alleviated diarrhea, decreased the lactulose/mannitol ratio (L/M) in the urine, increased the ileal villus height and upregulated the expression of Occludin in the ileal tissue and the effect was even better than high concentration of ZnO. Importantly, C_ZnO also regulated the intestinal flora, enriching Streptococcus and Lactobacillus and removing Bacillus and intestinal disease associated pathogens, including Clostridium_sensu_stricto_1 and Cronobacter in the ileal lumen. Although colonic microbiota remained relatively stable, marked rise of Blautia, a potential probiotic related to body health, could still be found. In addition, C_ZnO also led to significant increase of acetate and propionate in both foregut and hindgut. Collectively, low concentration of C_ZnO could effectively promote growth performance and reduce diarrhea through improving small intestinal morphology and permeability, enhancing the barrier function, adjusting the structure of gut microbiota and raising the concentration of short chain fatty acids (SCFAs) in weaned piglets.